PEMBENTUKAN KARAKTER MAHASISWA MELALUI PENDIDIKAN FILSAFAT ISLAM; PERSPEKTIF EPISTEMOLOGIS DAN PRAKTIK PENDIDIKAN DI STAI AL WASHLIYAH BARABAI - Nuthpaturahman (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study describes the relationship between understanding the concepts of Islamic philosophy and the development of character values such as honesty, responsibility, empathy, and integrity. This research method is descriptive qualitative with a case study approach, involving participant observation, and interviews with 30 students, 3 lecturers, and 3 education administrators. The results of the study indicate that Islamic philosophy education that integrates theory and practice can increase students' awareness of Islamic values and develop critical thinking skills in facing the challenges of the times. These findings also reveal that the implementation of Islamic philosophy education in the field still faces obstacles related to curriculum, teaching methods, and institutional support.